Associações espaciais entre indivíduos de diferentes espécies de Miconia spp. Ruiz & Pav. (Melastomataceae) - Higuchi, Pedro (2011)
The objective of this study was to evaluate spatial association of individuals of all genus Miconia spp. tree species established in the understory of an experimental plantation of Eucalyptus and Corymbia species. As most Miconia species are considered pioneers species, the tested hypothesis was that the analyzed species pairs presented individuals with total or partial habitat overlapping. Considering the history of the area, it is possible to assume that all individuals regenerate from the rain and the seed bank. It was established a transect crossing the study area toward its longest length from where it was determined the coordinates of individuals from Miconia genus with DSL (diameter at soil level) greater or equal to 1 cm. Spatial association among individual from different species were analyzed through bivariate Ripley's K function. It was sampled the following species: Miconia pepericarpa DC., Miconia sellowiana Naudin, Miconia albicans Triana, Miconia argyrophylla DC., Miconia chartacea Triana and Miconia cinnamomifolia (DC.) Naudin. Overall, the results demonstrated the lack of negative spatial association between species pairs, indicating that Miconia spp. individuals share partially or totally the same space in a eucalyptus plantation understory. Although the results cannot be extrapolated to other species, they support the idea that some pioneer species tend to coexist in tropical forests, in areas with high light availability.